Effect of Varying Oil Types on Physicochemical Properties and Sensory Evaluation of Pumpkin Seed Spread - Baharudin, Nurul Shahanim; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
In recent years, the popularity of plant-based spread, or butters has grown significantly due to increasing consumer demand for healthier food options. This study focused by utilizing pumpkin seed as one of the new alternative and healthy option for nut spread that derives form seeds. Pumpkin seeds are a great source of vitamins, minerals, unsaturated fats, and essential amino acids that are suitable to be one of the healthier options. This spread not only great option for those with nut allergies but also suitable for vegan and gluten free diets. The purpose of this study is to evaluate the physicochemical properties and sensory evaluation of pumpkin seed spreads that formulated with three different oils which were palm, corn and olive oil. The physicochemical properties were conducted to determine the moisture content, pH, total sugar content, colour measurement and firmness of the pumpkin seed spread. According to the result, the firmness of the pumpkin seed spread is the most critical factor influencing its Spreadability. The most favourable sample among the seven samples was sample 6, which contains 6% of palm and olive oil with value of firmness 22.26 N. The sample that consists of 6% of palm and olive oil was the easiest to spread compared to the others formulation. Besides, the sensory evaluation was conducted to analysed consumer preference based on Spreadability and overall acceptance. Sensory was carried in 9-point hedonic scale for rating the samples and t-test analysis was showed that consumer more preferred on sample 6. There were no significant differences in terms of appearance, colour and aroma where (p>0.05). In terms of Spreadability, flavour, texture and overall acceptance showed significance differences where (p